Exosomes Derived from CXCR4-Overexpressing BMSC Promoted Activation of Microvascular Endothelial Cells in Cerebral Ischemia/Reperfusion Injury - Xutong Li; Ye Zhang; Yong Wang; Dan Zhao; Chengcheng Sun; Shaoting Zhou; Dongsheng Xu; Jing Zhao (Neural Plasticity)
Background. Ischemic stroke is a severe acute cerebrovascular disease which can be improved with neuroprotective therapies at an early stage. However, due to the lack of effective neuroprotective drugs, most stroke patients have varying degrees of long-term disability. In the present study, we investigated the role of exosomes derived from CXCR4-overexpressing BMSCs in restoring vascular function and neural repair after ischemic cerebral infarction. Methods. BMSCs were transfected with lentivirus encoded by CXCR4 (BMSCCXCR4). Exosomes derived from BMSCCXCR4 (ExoCXCR4) were isolated and characterized by transmission electron microscopy and dynamic light scattering. Western blot and qPCR were used to analyze the expression of CXCR4 in BMSCs and exosomes. The acute middle cerebral artery occlusion (MCAO) model was prepared, ExoCXCR4 were injected into the rats, and behavioral changes were analyzed. The role of ExoCXCR4 in promoting the proliferation and tube formation for angiogenesis and protecting brain endothelial cells was determined in vitro. Results. Compared with the control groups, the ExoCXCR4 group showed a significantly lower mNSS score at 7 d, 14 d, and 21 d after ischemia/reperfusion (P<0.05). The bEnd.3 cells in the ExoCXCR4 group have stronger proliferation ability than other groups (P<0.05), while the CXCR4 inhibitor can reduce this effect. Exosomes control (ExoCon) can significantly promote the migration of bEnd.3 cells (P<0.05), while there was no significant difference between the ExoCXCR4 and ExoCon groups (P>0.05). ExoCXCR4 can further promote the proliferation and tube formation for the angiogenesis of the endothelium compared with ExoCon group (P<0.05). In addition, cobalt chloride (COCl2) can increase the expression of β-catenin and Wnt-3, while ExoCon can reduce the expression of these proteins (P<0.05). ExoCXCR4 can further attenuate the activation of Wnt-3a/β-catenin pathway (P<0.05). Conclusions. In ischemia/reperfusion injury, ExoCXCR4 promoted the proliferation and tube formation of microvascular endothelial cells and play an antiapoptotic role via the Wnt-3a/β-catenin pathway.